Antoinette - DiPucchio, Kelly (Atheneum Books for Young Readers, 2017)
"Raised in a family of talented bulldogs, Antoinette the poodle wonders what makes her special. She gets the chance to prove herself and find what she's good at when puppy Ooh-la-la goes missing"--